Multineutrosophic Analysis of the Relationship Between Survival and Business Growth in the Manufacturing Sector of Azuay Province, 2020–2023, Using Plithogenic n-Superhypergraphs - Eduardo Martín Campoverde Valencia; Jessica Paola Chuisaca Vásquez; Francisco Ángel Becerra Lois (Neutrosophic Sets and Systems)
This study analyzed the relationship between survival and business growth in the manufacturing sector of Azuay Province. To achieve this, Plithogenic n-SuperHyperGraphs and Multineutrosophic logic were employed to examine financial data defined by a set of n-indicators, n-records, and n-entities between 2020 and 2023. Additionally, the Springate Z-Score model was used, along with the logarithmic variation of assets, multiple regression, and factor analysis. The results showed that business survival was determined by variables related to vertices of financial stability and operational efficiency, while growth was primarily associated with asset expansion. Factor analysis identified three key components: firm size, financial solvency, and profitability, grouped within the dominant vertex. These findings demonstrate an integrated financial structure underlying business survival. In conclusion, the results provide an empirical basis for designing sustainability strategies in Azuay’s manufacturing sector, with potential applications in other regions and sectors of Ecuador.